Analysis of polygamy provision under the Islamic Family Law (Federal Territories) Act 1984; with referrence to the Qur’an and Sunnah - Fatah Yasin, Raudlotul Firdaus (International Islamic University Malaysia, 2010)
Islam permits polygamy to preserve woman's dignity and cares for the social moral and economic well-being of wives and orphans. Unfortunately, a number polygamous marriage among Muslims in Malaysia is dramatically misleading from both Islamic theories as well as principles. Hence, it has become a very controversial issue among its critics and supporters which resulting in serious criticism on the credibility of Islamic Family Law Act 1984.(ILLA) As a short term measure, a reform the IFLA has been suggested to focus more on specific legal mechanisms in curbing abuse of polygamy. In this paper the author attempts to analyze the synchronization of the IFLA in the light of Qur’an and Sunnah in order to suggest more effective, practical, and acceptable solutions in overcoming the issues and complying with the requirements by ‘following the real teaching in the revelation.’